What patients with pulmonary fibrosis and their partners think: a live, educative survey in the Netherlands and Germany - Manen, Mirjam J. G. van; Kreuter, Michael; Oltmanns, Ute; Palmowski, Karin; Brunnemer, Eva; Hummler, Simone (ERJ Open Research, 2017)
Pulmonary fibrosis greatly impacts patients and their partners. Unmet needs of patients are increasingly acknowledged; the needs of partners often remain unnoticed. Little is known about the best way to educate patients and partners. We investigated pulmonary fibrosis patients' and partners' perspectives and preferences in care, and the differences in these between the Netherlands and Germany. Additionally, we evaluated whether interactive interviewing could be a novel education method in this population. Patients and partners were interviewed during pulmonary fibrosis patient information meetings. In the Netherlands, voting boxes were used and results were projected directly. In Germany, questionnaires were used. In the Netherlands, 278 patients and partners participated; in Germany, 51. Many participants experienced anxiety. Almost all experienced misunderstanding, because people do not know what pulmonary fibrosis is. All expressed a need for information, psychological support and care for partners. Use of the interactive voting system was found to be pleasant (70%) and informative (94%). This study improves the knowledge of care needs of patients with pulmonary fibrosis and their partners. There were no major differences between the Netherlands and Germany. Interactive interviewing could be an attractive method to acquire insights into the needs and preferences of patients and partners, while providing them with information at the same time. Tweetable abstract ERSpublications click to tweetThe needs of patients with pulmonary fibrosis and partners, and the value of interactive interviewing http://ow.ly/M02t307jdEh